Isolation and Characterization of a Rolling-Circle-Type Plasmid from Rhodococcus erythropolis and Application of the Plasmid to Multiple-Recombinant-Protein Expression - Nakashima, Nobutaka (American Society for Microbiology, 2004)
We isolated, sequenced, and characterized the cryptic plasmid pRE8424 from Rhodococcus erythropolis DSM8424. Plasmid pRE8424 is a 5,987-bp circular plasmid; it carries six open reading frames and also contains cis-acting elements, specifically a single-stranded origin and a double-stranded origin, which are characteristic of rolling-circle-replication plasmids. Experiments with pRE8424 derivatives carrying a mutated single-stranded origin sequence showed that single-stranded DNA intermediates accumulated in the cells because of inefficient conversion from single-stranded DNA to double-stranded DNA. This result indicates that pRE8424 belongs to the pIJ101/pJV1 family of rolling-circle-replication plasmids. Expression vectors that are functional in several Rhodococcus species were constructed by use of the replication origin from pRE8424. We previously reported a cryptic plasmid, pRE2895, from R. erythropolis, which may replicate by a θ-type mechanism, like ColE2 plasmids. The new expression vectors originating from pRE8424 were compatible with those derived from pRE2895. Coexpression experiments with these compatible expression vectors indicated that the plasmids are suitable for the simultaneous expression of multiple recombinant proteins.